Ekofeminisme dalam Novel Dia adalah Kakakku Karya Tere Liye: Kajian Ekofeminisme Vandana Shiva - Rihada Aisy; Sarwiji Suwandi (CV. Alim's Publishing, 2026)
This study aims to describe the representation of ecofeminist values ​​in Tere Liye's novel